An alternative three-factor model for international markets: Evidence from the European Monetary Union - Ammann, Manuel; Odoni, Sandro; Oesch, David (Journal of Banking & Finance, 2012)
In this paper, we construct the three-factor model introduced by Chen et al. (2010) for a European sample covering 10 countries from the European Monetary Union and the period from 1990 to 2006. Two key findings result. First, we show that the properties of the European factors are comparable to those of the US factors. Second, we show that the alternative three-factor model’s explanatory power is either equal or superior to the explanatory power of traditional models when applied to five commonly known stock market anomalies. Our results thus suggest the use of international versions of the Chen et al. (2010) factor model in addition to traditional factor models in international empirical finance research.